Is cannabis use associated with less opioid use among people who inject drugs?. (1st August 2015) - Kral, Alex H.; Wenger, Lynn; Novak, Scott P.; Chu, Daniel; Corsi, Karen F.; Coffa, Diana; Shapiro, Brad; Bluthenthal, Ricky N.
Highlights: People who inject drugs (PWID) were recruited using targeted sampling in Los Angeles and San Francisco, CA. About one-half of PWID reported cannabis use in the past 30 days. PWID who use cannabis used opioids less often than those who did not use cannabis. Abstract: Background: Clinical, experimental, and ethnographic research suggests that cannabis may be used to help manage pain. Ethnographic research has revealed that some people are using cannabis to temper their illicit opioid use. We seek to learn if there is an association between cannabis use and the frequency of nonmedical opioid use among people who inject drugs (PWID). Methods: PWID were recruited using targeted sampling methods in Los Angeles and San Francisco, California, 2011–2013. We limited analysis to people who used opioids in past 30 days ( N = 653). Outcome variable: number of times used any opioids non-medically in past 30 days. Explanatory variable: any cannabis use past 30 days. Statistics: multivariable linear regression with a log-transformed outcome variable. Results: About half reported cannabis use in the past 30 days. The mean and median number of times using opioids in past 30 days were significantly lower for people who used cannabis than those who did not use cannabis (mean: 58.3 vs. 76.4 times; median: 30 vs 60 times, respectively; p < 0.003). In multivariable analysis, people who used cannabis used opioids less often than those who did not use cannabis (Beta: −0.346; 95% confidence interval: −0.575, −0.116; p < 0.003). Conclusions: There is a statistical association between recent cannabis use and lower frequency of nonmedical opioid use among PWID. This may suggest that PWID use cannabis to reduce their pain and/or nonmedical use of opioids. However, more research, including prospective longitudinal studies, is needed to determine the validity of these findings.